Fast DNA Diagnostic Using Fe3O4 Magnetic Nanoparticles and Light Emitting ZnS/Mn Nanoparticles - Quynh, Luu Manh; Hieu, Nguyen Minh; Nam, Nguyen Hoang (VNU Journal of Science: Mathematics - Physics, 2014)
Abstract: In this study, the fast DNA diagnostics was successfully developed using high fluorescent Mn doped ZnS nanoparticles and NH 2 -modified SiO 2 coated Fe 3 O 4 nanoparticles in a sandwich structure . In one end of the sandwich structure, we employed NH 2 -modified SiO 2 coated Fe 3 O 4 nanoparticles as a docking matrix. A so-called capture probe oligonucleotide chain, that specifically identifies the target DNA, linked to the docking magnetic particles. In the other end, other oligonucleotide chain – named detector probe – contacted with the signaling semiconductor particles. The complementary hybridization of the detector probe – target – capture probe formed the sandwich configuration that attached the fluorescent particles to the docking matrix. This configuration was used to detect DNA of Epstein-Bar virus (EBV) and as the result, a fine affinity between the luminescent intensity at 586 nm of Mn doped ZnS colloids showed with the initially added DNA target concentration, which could detect the presence of target DNA within 2×10 6 copies/ml (~0.3 fM). The mobility of the as-prepared solutions used in this methodology promised an attractive applicability for designing a DNA detecting fast KIT. Keywords: DNA fast kit, ZnS nanoparticles, Fe3O4 nanoparticles, Fluorescent.